Implementation Of Steam Model To Increase Student Engagement Through Lesson Study - Suharniwati, Suharniwati; Nuraini, Nuraini; Sapariah, Sapariah; Zulkarnain, Amri; Rusdan, Rusdan; Hadi, M. Alpan; Khaerudin, Khaerudin (Sumber Belajar Sejahtera, 2024)
Lesson Study is conducted to improve students' understanding through collaborative learning approach. The purpose of this study is to apply the STEAM model in improving students' understanding at SDN 4 Jerowaru. This research methodology uses qualitative methods. The techniques used to collect data in this study were adjusted to the type of data taken, namely (1) observation, (2) rubrics, (3) tests, and (4) documentation, taking pictures by researchers to strengthen the data obtained in learning activities. The data analysis technique used in this research is qualitative descriptive technique. The results of this study In cycle I of the learning process activities or at the do stage showed that students still did not look active and their creative thinking skills were still not very significant, so a reflection was carried out by the model teacher to plan the plan process in cycle II, several improvements were made by changing the methods used and learning materials. Furthermore, at the do stage of cycle II, student activities have looked very active, collaboration between groups has been active, besides that students' creative thinking skills have increased significantly.